Trabecular bone score in type 1 diabetes—a cross-sectional study. Issue 1 (January 2016) - Neumann, T.; Lodes, S.; Kästner, B.; Lehmann, T.; Hans, D.; Lamy, O.; Müller, U.; Wolf, G.; Sämann, A.
Abstract Summary Trabecular bone score (TBS) seems to provide additive value on BMD to identify individuals with prevalent fractures in T1D. TBS did not significantly differ between T1D patients and healthy controls, but TBS and HbA1c were independently associated with prevalent fractures in T1D. A TBS cutoff <1.42 reflected prevalent fractures with 91.7 % sensitivity and 43.2 % specificity. Introduction Type 1 diabetes (T1D) increases the risk of osteoporotic fractures. TBS was recently proposed as an indirect measure of bone microarchitecture. This study aimed at investigating the TBS in T1D patients and healthy controls. Associations with prevalent fractures were tested. Methods One hundred nineteen T1D patients (59 males, 60 premenopausal females; mean age 43.4 ± 8.9 years) and 68 healthy controls matched for gender, age, and body mass index (BMI) were analyzed. The TBS was calculated in the lumbar region, based on two-dimensional (2D) projections of DXA assessments. Results TBS was 1.357 ± 0.129 in T1D patients and 1.389 ± 0.085 in controls (p  = 0.075). T1D patients with prevalent fractures (n  = 24) had a significantly lower TBS than T1D patients without fractures (1.309 ± 0.125 versus 1.370 ± 0.127, p  = 0.04). The presence of fractures in T1D was associated with lower TBS (odds ratio = 0.024, 95 % confidence interval (CI) = 0.001–0.875;p  = 0.042) but not with age or BMI. TBS and HbA1c were independently associated with fractures. The area-under-the curve (AUC) of TBS was similar to that of total hip BMD in discriminating T1D patients with or without prevalent fractures. In this set-up, a TBS cutoff <1.42 discriminated the presence of fractures with a sensitivity of 91.7 % and a specificity of 43.2 %. Conclusions TBS values are lower in T1D patients with prevalent fractures, suggesting an alteration of bone strength in this subgroup of patients. Reliable TBS cutoffs for the prediction of fracture risk in T1D need to be determined in larger prospective studies.